Immigrants, Multiculturalism, and Expensive Cultural Tastes: Quong on Luck Egalitarianism and Cultural Minority Rights - Lippert-Rasmussen, Kasper (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique de l’Université de Montréal, 2011)
Kymlicka has offered an influential luck egalitarian justification for a catalogue of polyethnic rights addressing cultural disadvantages of immigrant minorities. In response, Quong argues that while the items on the list are justified, in the light of the fact that the relevant disadvantages of immigrants result from their choice to immigrate, (i) these rights cannot be derived from luck egalitarianism and (ii) that this casts doubt on luck egalitarianism as a theory of cultural justice. As an alternative to Kymlicka’s argument, Quong offers his own justification of polyethnic rights based on a Rawlsian ideal of fair equality of opportunity. I defend luck egalitarianism against Quong’s objection arguing that if choice ever matters, it matters in relation to cultural disadvantages too. Also, the Rawlsian ideal of fair equality of opportunity cannot justify the sort of polyethnic rights that Quong wants it to justify, once we set aside an unwarranted statist focus in Quong’s conception of fair equality of opportunity. Whatever the weaknesses of luck egalitarianism are, the inadequacy of the position in relation to accommodating cultural disadvantages of immigrants is not among them.